POLITIK HUKUM PP NOMOR 78 TAHUN 2015 TENTANG PENGUPAHAN SEBAGAI UPAYA PEMENUHAN HAK DASAR PEKERJA/BURUH - Nadhiroh, Anis Nur; Shobahah, Nurush (UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
This research will be more directed to respond to PP Number 78 of 2015 concerning Wages. In this PP on Wages, it has contradicted the ideals in the constitution, so that in the hierarchy of statutory regulations, the wage formula in this PP on Wages has contradicted the principle of Lex Specialis Derogate Legi Inferiori. The big idea that is being promoted is about efforts to create ideal and just laws in accordance with the values ​​and ideals of the state. These efforts are often referred to as Legal Politics. Then it is often misunderstood as legislative (legal) politics, because it is attached to legislative variables where the tracing process is often carried out normatively by examining the legal ideals of a nation and its achievement efforts which are stated in the work plan (legal politics) of the legislative institution in the form of Prolegnas. The method used in this study is normative juridical. The results of this study convey that in the process of determining the amount of wages, it has ignored the amount of fair and decent wages for workers both from positive law and Islamic law.